Animation and child: Reading in social, cultural, moral, and religious influences. - لامية طالة (International Journal of Social Communication, 2022)
Animation programs have multiple effects on children's lives, and thus serve as a cultural medium, educational, cultural and recreational tool that serves as a source of knowledge and as a means to promote children's social and cultural development. All of the content of the cartoons provides them with images of the values, trends and beliefs they must have, thereby instilling ideas, behaviors and values that are rooted in their minds and are age-specific. - Animation - plays a role parallel to that of parents in the development of a child's values acquired by his or her family, helping to develop his or her personality in mental, motor, linguistic, emotional, and social terms. This is why your parents should be aware of the use of the programs offered to promote the use of lessons learned when watching these drawings. Arab animations must also be supported by the creation of special films for our Arab children to develop the values, principles and ideals derived from our culture.